HISTO-MORPHOLOGICAL STUDY OF IMMUNE CELLS IN CAECUM OF DIFFERENT POULTRY BIRDS - M. R. SENAPATI; P. C. BEHERA; A. MAITY; A. K. MANDAL; A. K. KUNDU (The Bioscan, 2015)
The present research was carried out to have comparative study of the histological architecture of the caecum of different poultry birds. The study was carried out on six numbers of adult birds of quail, chicken and duck of both sex of 4-6 wks, 3-4 months and 8-10 months of age respectively without any detectable abnormalities. The mucosal surface of quail caecum showed highly developed flat areas and ridges pattern of villi whereas in chicken and duck, the mucosa was having more prominent tooth-shaped villi. Significantly (p< 0.05) greater villi heights (in μm) was observed in chicken (246.48± 26.03) than the quail (177.11± 4.69) and duck (130.67± 6.77). The thickness of the caecal wall (in μm) was significantly (p< 0.05) higher in chicken (147.57± 9.27) followed by duck (114.44± 5.20) and quail (96.88±4.62). Diffuse sub epithelial immune cells of chicken and duck caecum fill the lamina propria layer. Distinct lymphoid nodules surrounded by capsular connective tissues were noticed deep inside the villous core in chicken only. The results of the present study could be helpful to understand the affection of immune tissue due to diseases and abiotic factors as the caecum plays a vital role in immunological surveillance against foreign microorganism.